2006
DOI: 10.1111/j.1745-459x.2006.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensorial Characteristics During Ripening of the Murcia Al Vino Goat's Milk Cheese: The Effect of the Type of Coagulant Used and the Size of the Cheese

Abstract: The aim of the present work was to study the sensorial characteristics of Murcia al Vino cheese made with different coagulants (animal rennet and powdered vegetable coagulant obtained from cardoon [Cynara cardunculus]) and of different weights (1 and 3 kg). The cheeses made with rennet showed less odor and taste intensities, a bit clearer color and were harder and grainier, but less creamy than the cheeses made with vegetable coagulant. The big cheeses were characterized by high wine odor, acid odor, wine tast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 18 publications
5
29
1
Order By: Relevance
“…A positive correlation (po0.05) was previously detected between the HO concentration and the HO/HI ratio and the bitter taste of the cheeses (data reported by Tejada et al, 2006), which is in agreement with other reports in ewes' milk cheese (Go´mez, Gaya, Nu´n˜ez, & Medina, 1996). Nevertheless, after 45 days of ripening (the period in which the cheese is available for purchase), no significant differences were detected between the bitter taste of cheeses made with PC and AR (Tejada et al, 2006).…”
Section: Changes In the Hi And Ho Peptidessupporting
confidence: 93%
See 3 more Smart Citations
“…A positive correlation (po0.05) was previously detected between the HO concentration and the HO/HI ratio and the bitter taste of the cheeses (data reported by Tejada et al, 2006), which is in agreement with other reports in ewes' milk cheese (Go´mez, Gaya, Nu´n˜ez, & Medina, 1996). Nevertheless, after 45 days of ripening (the period in which the cheese is available for purchase), no significant differences were detected between the bitter taste of cheeses made with PC and AR (Tejada et al, 2006).…”
Section: Changes In the Hi And Ho Peptidessupporting
confidence: 93%
“…Nevertheless, after 45 days of ripening (the period in which the cheese is available for purchase), no significant differences were detected between the bitter taste of cheeses made with PC and AR (Tejada et al, 2006). However, Agboola et al (2004), did not detect a significant correlation between bitterness scores and HO in ewes' milk cheese.…”
Section: Changes In the Hi And Ho Peptidescontrasting
confidence: 64%
See 2 more Smart Citations
“…The cheeses made with GP had a more uniform and softer body and texture. In a previous study, it was observed that Murcia al Vino cheese made with animal rennet was significantly harder (P<0.01), more grainy (P<0.001), and less creamy (P<0.001) than the same cheese made using plant coagulant (Tejada et al 2006). Similar findings have been reported for ewe's milk cheeses made using vegetable coagulant from C. cardunculus, which were softer and creamier than those made using rennet (Tejada et al 2007).…”
Section: Sensory Characteristicsmentioning
confidence: 93%